Effectiveness of Core-Shell Nanofibers Incorporating Amphotericin B by Solution Blow Spinning Against Leishmania and Candida Species - Gonçalves, Ingrid Morgana Fernandes; Rocha, Ítalo Martins; Pires, Emanuene Galdino; Muniz, Isis de Araújo Ferreira; Maciel, Panmella Pereira; de Lima, Jefferson Muniz; dos Santos, Iêda Maria Garcia; Batista, Roberta Bonan Dantas; de Medeiros, Eudes Leonnan Gomes; de Medeiros, Eliton Souto; de Oliveira, Juliano Elvis; Goulart, Luiz Ricardo; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
The aim of this study was to develop polymeric nanofibers for controlled administration of Amphotericin B (AmpB), using the solution centrifugation technique, characterizing its microstructural and physical properties, release rate, and activity against Leishmania and Candida species. The core-shell nanofibers incorporated with AmpB was synthesized by Solution Blow Spinning (SBS) and characterized by scanning electron microscopy (SEM), differential scanning calorimetry, X-Ray diffraction, drug release assay. In vitro leishmanicidal and antifungal activity were also evaluated. Fibrous membranes with uniform morphology and smooth surfaces were produced. The intensity of the diffraction peaks becomes slightly more pronounced, assuming the increased crystallization in PLA/PEG at high AmpB loadings. Drug release happened and the solutions with nanofibers to greater incorporation of AmpB showed a higher concentration. In the results of the experiment with promastigotes, the wells treated with nanofibers containing concentration of AmpB at 0.25%, 0.5% and 1%, didn’t have any viable cell, similar to the positive control. Various concentrations of AmpB improved inhibition of fungal growth. The delivery system based on PLA/PEG nanofiber was properly developed for AmpB, presenting a controlled release and a successful encapsulation, as well as antifungal and antileishmanial activity.